Installation and the moving image - Elwes, Catherine (Columbia University Press, 2015)
Architecture -- Painting -- Performance -- Film history -- Film as film -- Structural film : detractions and revisions -- The dialectics of spectatorship -- Expanded cinema -- Sound -- Video installation -- Closing thoughts.